Isabella the air fairy - Meadows, Daisy (Scholastic Inc., 2014)
"The air on Rainspell Island is thick with smog. Isabella the Air Fairy wants to return the island's fresh ocean breezes and sparkling blue skies. But she can't do anything without her wand!"--